Revision of the genus Myrmecobrenthus Kleine with a description of a new species from Gabon (Coleoptera: Brentidae: Eremoxenini) - Bartolozzi, Luca; Loudit, Sandrine Mariella Bayendi (Zootaxa, 2011)
The genus Myrmecobrenthus Kleine, 1920 is revised and a key for the species of this genus is provided. Myrmecobrenthus susinii sp. nov. is described from Gabon, and compared with the closely related M. ater Damoiseau, 1961 and M. wasmanni Kleine, 1920, from which it mainly differs in the shape of the male head and rostrum. Myrmecobrentus wasmanni is recorded for the first time from Gabon.